THE EFFECT OF PLANNING, FERTILIZER INVENTORY CONTROL, AND SUSTAINABILITY REPORTS ON PALM OIL SEEDLING SALES AT CV. TRANS BAROKAH MANDIRI - Khayrani, Putri Afifah; Tripermata, Lukita; Putri, Andini Utari (JEA17: Jurnal Ekonomi Akuntansi, 2025)
Fertilizer inventory planning and control are crucial aspects in improving the effectiveness of distribution and sales of oil palm seedlings. This study aims to analyze the effect of fertilizer inventory planning, fertilizer inventory control, and sustainability reports on the sales of oil palm seedlings at CV. Trans Barokah Mandiri. This research was conducted in Palembang City using a quantitative descriptive research method. The population in this study consists of fertilizer inventory reports from 2021 to 2023 at CV. Trans Barokah Mandiri, with a sample size of 36, obtained from a total research period of three years (2021-2023) with data division based on months, i.e., 12 months per year. Data were analyzed using multiple linear regression with SPSS version 26. The results showed that partially, fertilizer inventory planning had a significant effect on the sales of oil palm seedlings, while fertilizer inventory control and sustainability reports did not have a significant effect. Simultaneously, the three independent variables had a significant effect on the sales of oil palm seedlings.